2022
DOI: 10.1021/acs.macromol.2c00264
|View full text |Cite
|
Sign up to set email alerts
|

Precise Synthesis of Structurally Diverse Aggregation-Induced Emission-Active Polyacrylates by Cu(0)-Catalyzed SET-LRP with Macromolecular Structure-Correlated Emission

Abstract: The rational design and precise synthesis of aggregation-induced emission (AIE) active polymers with diverse macromolecular structures are crucial to their applications in various fields. Herein, four tetraphenylethylene (TPE) bromopropionate initiators with the number of initiation sites of n = 1−4 were synthesized for the first time and applied in the Cu(0)-mediated single-electron transfer living radical polymerization (SET-LRP) of methyl acrylate (MA) and tert-butyl acrylate (tBA). Well-controlled polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…It is striking that the three TPE-appended maleic acid terpolymers exhibited a widely varied response to Ca 2+ . hPTSM-39 displayed the largest dynamic range (86), which was much higher that of hPTVM-39 (17) and hPTSM-39 (15). This is consistent with the highest chain rigidity and strongest aromatic ring-involved intramolecular interactions of hPTSM-39.…”
Section: Synthesis Of the Tpe-containing Monomers Tpe-appended Maleic...supporting
confidence: 68%
See 1 more Smart Citation
“…It is striking that the three TPE-appended maleic acid terpolymers exhibited a widely varied response to Ca 2+ . hPTSM-39 displayed the largest dynamic range (86), which was much higher that of hPTVM-39 (17) and hPTSM-39 (15). This is consistent with the highest chain rigidity and strongest aromatic ring-involved intramolecular interactions of hPTSM-39.…”
Section: Synthesis Of the Tpe-containing Monomers Tpe-appended Maleic...supporting
confidence: 68%
“…Recently, aggregation-induced emission luminogens (AIEgens) have been utilized in developing stimuli-responsive AIE-active polymer systems. Owing to their inherent high sensitivity to the aggregated state dictated by their surrounding environment, AIEgens play the dual roles of “stimuli acceptor” and “signaling module” in the system. This often gives rise to intriguing stimuli-responsive fluorescence performance, contrasting to the case of traditional fluorophores with the troublesome aggregation-caused quenching effect.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study was performed between pristine DOX solution as the control and TPE-PEGA-Hyd-DOX solutions at the same concentration, where drug release reached only 10% after 96 hours under normal cell conditions compared with 40% after 24 hours under cancer cell conditions helps confirmed that conjugation of DOX to the drug carrier controls the release of DOX and protects normal cells against DOX. Many other studies also employed the Cu(0)-RDRP methods to synthesize AIE polymers such as Cu(0)-catalyzed SET-LRP reported by Wang, Yang and co-workers for the study of multi-arm star polymers with TPE-functionalized core, [183] and the study of through-space charge-transfer thermally activated delayed fluorescence (TSCT-TADF) phenomenon using AIE-functionalized monomers. [184][185][186] NMP can also be used for the synthesis of AIE polymers with a unique morphology as demonstrated by Nicolas and co-workers in 2017, whom employed carbodiimide chemistry to link 4-(N -methylpiperazine)-1,8-naphthalimide-based AIE dye, [187] with AMA-SG1 alkoxyamine, yielding Napht-AMA-SG1 in 82% yield via the grafting from or 'drug-initiated' method.…”
Section: Aie Polymers Via Other Rdrp Methodsmentioning
confidence: 99%
“…and easily removing catalyst. [43][44][45][46][47] Notably, SET-LRP is highly sensitive for monomers, initiators, and ligands. The matching of initiators and ligands affects the controllability SET-LRP of methyl methacrylate (MMA).…”
Section: Introductionmentioning
confidence: 99%
“…Single‐electron transfer mediated living radical polymerization (SET‐LRP) was selected to validate our hypothesis due to its unique advantages, such as high end‐group fidelity, fast polymerization rate, and easily removing catalyst. [ 43–47 ] Notably, SET‐LRP is highly sensitive for monomers, initiators, and ligands. The matching of initiators and ligands affects the controllability SET‐LRP of methyl methacrylate (MMA).…”
Section: Introductionmentioning
confidence: 99%